The use of the image as a research tool - García Gil, Mónica Eliana (Universidad Santo Tomás, 2013)
Based on the research entitled “Equity and city coexistence in Bogota´s public space: contributions to teaching and urban management” (Universidad Pedagógica Nacional and Universidad Santo Tomás, Bogotá, 2007-2009), this article analyzes the methodology that attempts to establish narratives that circulated among youth groups in Bogotá. It also evaluates its contributions to the creation of coexistence and equity in the public space. It is worth to state that the research mentioned attempted to identify characteristics of different population groups in the city, and how they could be classified as favorable to equity in access, use of public space and coexistence among citizens.